Optimization of a Cold storage using Taguchi Methodology - , Santanu Dey, Dr.Nimai Mukhopadhyay (International Journal of Scientific Research and Management (IJSRM), 2014)
T:In this project work design of experiments have used to optimize various control factors so as the heat gain inthecold room or in the other words the heat flow from the outside ambience to the inside of the cold room will beminimum.Taguchi orthogonal array have used as a design of experiments. Three control factors with three levels of eachhave been chosenfor analysis. The control factors are insulation thickness of the side walls (TW), area of the side walls (AW),and insulationthickness of the roof (TR). Different amount of heat gains in the cold room for different set of test runs havetaken as the outputparameter. The objective of this work is to find out the optimum setting of the control factors or designparameters so as theheat gain in the cold room will be minimum. The Taguchi S/N ratio analysis have used as anoptimization technique. Smaller thebetter type S/N ratio have used for calculating the optimum level of control parameters.Analysis of variance ANOVA was alsoperformed on the test results to find out the significant control factors. After analysisthe results showed that the insulationthickness of the side walls (TW) was the most significant control factor followed by thearea of the wall (AW). Insulationthickness of the roof (TR) was not statistically significant.